2019
DOI: 10.3390/ijms20184402
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Fatty Acid-Derived Resolvin D2 Regulates Human Placental Vascular Smooth Muscle and Extravillous Trophoblast Activities

Abstract: Omega-3 fatty acids are important to pregnancy and neonatal development and health. One mechanism by which omega-3 fatty acids exert their protective effects is through serving as substrates for the generation of specialized pro-resolving lipid mediators (SPM) that potently limit and resolve inflammatory processes. We recently identified that SPM levels are increased in maternal blood at delivery as compared to umbilical cord blood, suggesting the placenta as a potential site of action for maternal SPM. To exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 48 publications
(64 reference statements)
1
11
0
Order By: Relevance
“…The polyunsaturated fatty acids (PUFAs) include omega-3 (α-linolenic acid, docosahexaenoic acid, and eicosapentaenoic acid) and omega-6 (linoleic acid/LA and arachidonic acid). 48 Several studies in animals have examined the effects of PUFAs on fecundity, maternal health, and neonatal development, 49,50 but very few studies evaluated the effect of PUFAs on the sex ratio. Curry 34 studied the effect of high-fat/lowcarbohydrate diet compared with low-fat/high-carbohydrate diet in Japanese quail and found that the high-fat/lowcarbohydrate diet had no effect on the sex ratio.…”
Section: Experimental Animal Studiesmentioning
confidence: 99%
“…The polyunsaturated fatty acids (PUFAs) include omega-3 (α-linolenic acid, docosahexaenoic acid, and eicosapentaenoic acid) and omega-6 (linoleic acid/LA and arachidonic acid). 48 Several studies in animals have examined the effects of PUFAs on fecundity, maternal health, and neonatal development, 49,50 but very few studies evaluated the effect of PUFAs on the sex ratio. Curry 34 studied the effect of high-fat/lowcarbohydrate diet compared with low-fat/high-carbohydrate diet in Japanese quail and found that the high-fat/lowcarbohydrate diet had no effect on the sex ratio.…”
Section: Experimental Animal Studiesmentioning
confidence: 99%
“…Thereby, the protective effects of omega-3 fatty acids have, at least in part, been attributed to SPM activity, and it has been suggested that SPMs are important for a healthy pregnancy. In this context, resolvin D2 has been found to alter the inflammatory response in human placental tissue [58] and increased resolvin D1 and D2 levels have been associated with infant neonatal intensive care unit admission, while decreased levels were associated with term birth (≥36 weeks of gestation) [59].…”
Section: Polyunsaturated Fatty Acids and Bioactive Lipid Mediators In Pregnancymentioning
confidence: 99%
“…GPR18 receptor protein was also detected in the cardiovascular system, including the heart [16], isolated vessels and endothelial cells of mesenteric arteries [17], retinal vessels of the rat [6], pulmonary arteries [18], and placental vascular smooth muscle of humans [19] as well as various vascular endothelial cell lines [6,20,21]. It was also found to be expressed in the rat's rostral ventrolateral medulla (RVLM), a brain region involved in the regulation of cardiovascular function [9].…”
Section: Introductionmentioning
confidence: 99%